Color Discrimination Is Affected by Modulation of Luminance Noise in Pseudoisochromatic Stimuli - Cormenzana Méndez, Iñaki; Martín, Andrés; Charmichael, Teaire L.; Jacob, Mellina M.; Lacerda, Eliza M. C. B.; Gomes, Bruno D.; Fitzgerald, Malinda E. C.; Ventura, Dora F.; Silveira, Luiz C. L.; O'Donell, Beatriz M.; Souza, Givago S. (Frontiers in psychology, 2016)
Pseudoisochromatic stimuli have been widely used to evaluate color discrimination and to identify color vision deficits. Luminance noise is one of the stimulus parameters used to ensure that subject's response is due to their ability to discriminate target stimulus from the background based solely on the hue between the colors that compose such stimuli. We studied the influence of contrast modulation of the stimulus luminance noise on threshold and reaction time color discrimination. We evaluated color discrimination thresholds using the Cambridge Color Test (CCT) at six different stimulus mean luminances. Each mean luminance condition was tested using two protocols: constant absolute difference between maximum and minimum luminance of the luminance noise (constant delta protocol, CDP), and constant contrast modulation of the luminance noise (constant contrast protocol, CCP). MacAdam ellipses were fitted to the color discrimination thresholds in the CIE 1976 color space to quantify the color discrimination ellipses at threshold level. The same CDP and CCP protocols were applied in the experiment measuring RTs at three levels of stimulus mean luminance. The color threshold measurements show that for the CDP, ellipse areas decreased as a function of the mean luminance and they were significantly larger at the two lowest mean luminances, 10 cd/m(2) and 13 cd/m(2), compared to the highest one, 25 cd/m(2). For the CCP, the ellipses areas also decreased as a function of the mean luminance, but there was no significant difference between ellipses areas estimated at six stimulus mean luminances. The exponent of the decrease of ellipse areas as a function of stimulus mean luminance was steeper in the CDP than CCP. Further, reaction time increased linearly with the reciprocal of the length of the chromatic vectors varying along the four chromatic half-axes. It decreased as a function of stimulus mean luminance in the CDP but not in the CCP. The findings indicated that visual performance using pseudoisochromatic stimuli was dependent on the Weber's contrast of the luminance noise. Low Weber's contrast in the luminance noise is suggested to have a reduced effect on chromatic information and, hence, facilitate desegregation of the hue-defined target from the background.